2021
DOI: 10.1093/g3journal/jkab253
|View full text |Cite
|
Sign up to set email alerts
|

Single-step genomic BLUP enables joint analysis of disconnected breeding programs: an example with Eucalyptus globulus Labill

Abstract: Single-step GBLUP (HBLUP) efficiently combines genomic, pedigree, and phenotypic information for holistic genetic analyses of disjunct breeding populations. We combined data from two independent multi-generational Eucalyptus globulus breeding populations to provide direct comparisons across the programs and indirect predictions in environments where pedigreed families had not been evaluated. Despite few known pedigree connections between the programs, genomic relationships provided the connectivity required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
(102 reference statements)
1
9
0
Order By: Relevance
“…This study used a subset of the E. globulus phenotype data analyzed by Callister et al (2021) . Full-sib family data for 13 progeny tests in the “Green Triangle” region of Australia were provided by 2 separate multigenerational commercial tree improvement programs, EG1 (Australian Bluegum Plantations) and EG2 (HVP Plantations) ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study used a subset of the E. globulus phenotype data analyzed by Callister et al (2021) . Full-sib family data for 13 progeny tests in the “Green Triangle” region of Australia were provided by 2 separate multigenerational commercial tree improvement programs, EG1 (Australian Bluegum Plantations) and EG2 (HVP Plantations) ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The authors suggested that true average relationships within races were probably substantially larger than those estimated in H and that accommodating ancestral race effects in HBLUP should be prioritized. The goals for the present study extend from this recent work ( Callister et al 2021 ) using a subset of their data. Our goals were to (1) fit models including MF and examine relationships corresponding to race, landrace, and plus tree (infusion) populations and (2) use the LR approach ( Legarra and Reverter 2018 ) to evaluate goodness of fit for genetic models with and without genomic relationship information, with genetic groups excluded or incorporated as UPGs, or as MFs.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations